ANALISIS IMPLEMENTASI PENYELENGGARAAN PENDIDIKAN INKLUSI PADA SEKOLAH MENENGAH ATAS DI KOTA PADANG - Kirana, Sella; Luthifah, Hasna; Ghina, Alifah Ratu; Wandraini, Azmi; Kencana, Melati Puspa; Rahmatika, Helsa (JPI (Jurnal Pendidikan Inklusi), 2023)
The aim of this research is to describe the implementation of inclusive education in Padang City, one of which is SMAN 7 Padang City. The research method uses qualitative research methods descriptive. The data collection technique was carried out by observation and interviews with resource persons, namely selected educators/counseling teachers teknik sampling purposive. The research results obtained are that the implementation created in inclusive education at SMAN 7 Padang City is running as it should, the school has succeeded in implementing inclusive education for children with special needs. Acceptance of children with special needs at SMAN 7 Padang City, namely ABK with disabilities and specific learning difficulties. ABK is accompanied by a special educator from the BK teacher. However, the GPK at SMAN 7 Padang City is not an expert educator from special education. The GPK at SMAN 7 Padang City is a teacher who has participated in an inclusive education training program and an internship at one of the State Special Schools in Padang City. The inclusive learning model is a regular class, where ABK learn with other general students. Keywords: Inclusive Education, Students with Special Needs, Special Assistant Teachers